Point pinning centers in SiC doped MgB2 wires after HIP. (16th June 2016) - Gajda, D; Zaleski, A; Morawski, A; Cetner, T; Thong, C J; Rindfleisch, M A
Abstract: In this study we show that dominant point pinning mechanisms in SiC doped MgB2 wires can be obtained by annealing in high isostatic pressure. The results indicate that the point pinning centers increase the critical current density in medium and high magnetic fields, but not at low magnetic fields. In addition, our study shows that dominant pinning mechanism changes from point to surface type with increase of magnetic fields. An MgB2 wire heat treated in a high pressure of 1.4 GPa shows a high critical current density of 100 A mm −2 in 13 T at 4.2 K. Scanning electron microscope studies show that high isostatic pressure increases the density of the MgB2 material, eliminates voids, allows for small Si precipitates and homogeneous distribution of Si precipitates. Transport measurements E - B and E - I show that the MgB2 wires manufactured by Hyper Tech Research did not heat up after transition into a normal state. This is important for applications in coils.